2013
DOI: 10.1007/s10620-013-2631-z
|View full text |Cite
|
Sign up to set email alerts
|

Inulin-Type Fructans with Different Degrees of Polymerization Improve Lipid Metabolism but Not Glucose Metabolism in Rats Fed a High-Fat Diet Under Energy Restriction

Abstract: Findings suggest that, depending on DP, dietary supplementation with inulin (DP 15 or DP 24) in rats fed a high-fat diet, regardless of food intake, positively modulates lipid metabolism and fecal microbiota but not glucose metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
28
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 39 publications
5
28
1
3
Order By: Relevance
“…Stewart and others also reported that short-chain inulin is fermented rapidly compared with longer-chain inulin (22). This is corroborated by our previous study, which also showed similar findings in animals fed DP 10, DP 15, and DP 24 inulins, where most of the low molecular weight inulin led to lower cecal SCFA concentrations than high molecular weight inulin (9). However, accumulated data from animal and in vitro studies suggest that there is considerable variation between inulin-type fructans in the rate of fermentation and the SCFAs produced.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Stewart and others also reported that short-chain inulin is fermented rapidly compared with longer-chain inulin (22). This is corroborated by our previous study, which also showed similar findings in animals fed DP 10, DP 15, and DP 24 inulins, where most of the low molecular weight inulin led to lower cecal SCFA concentrations than high molecular weight inulin (9). However, accumulated data from animal and in vitro studies suggest that there is considerable variation between inulin-type fructans in the rate of fermentation and the SCFAs produced.…”
Section: Discussionsupporting
confidence: 89%
“…Previously we have shown in rats that an inulin-type fructan (inulin-Tokachi, average DP of 15, range 2-60) was fermented throughout the colon more slowly than inulin-GR (average DP of 10) but faster than inulin-HP (average DP of 24) (9). This difference translated to in differences in the number of colonic microbial species and hypolipidemic response (9). …”
mentioning
confidence: 96%
“…Accordingly, changing the microbiota composition through direct administration of bacteria (probiotics) or indirect effect of prebiotics leads to weight loss [24]. In a recent study, the use of inulin has been shown to affect the gut microbiota of rats that were fed a high fat diet, and improve lipid metabolism [25]. Our results are similarly showing that inulin can correct an impaired lipid profile.…”
Section: Discussionsupporting
confidence: 66%
“…For example, these non-digestible carbohydrates have been demonstrated to reduce weight gain and related metabolic disorders via specific actions on food intake [57]. Most of these findings have been obtained following supplementation with inulin-type fructans from Jerusalem artichoke ( Helianthus tuberosus ) and chicory ( Cichorium intybus ) [8].…”
Section: Introductionmentioning
confidence: 99%